Conspiracy Theories and the Crisis of the Public Sphere: COVID-19 in Slovenia - Vidmar Horvat, Ksenija (Javnost-The Public, 2021)
This paper examines the rise of conspiracy theories amidst the 2020 global COVID-19 pandemic. Conspiracy theories have been a historic sojourner in Western modern societies, stretching from witch hunts in early modern Europe to the 1950s anti-communist witch hunt of the McCarthy era in the U.S. During the COVID-19 health crisis, however, the conspiracy theories have gained a fresh impetus, travelling globally and forming diverse communities of believers. Moreover, once a predominantly fringe phenomenon, at present, they have moved to the centre of the public debate, deliberating on the reliability of scientific evidence as well as the legitimacy of lockdowns and other public health measures. This makes the COVID-19 conspiracy believers an integral part of the public sphere where, in open conflict with expert knowledge and science, they act as a “pandemic counter-public.” I observe the rise of this pandemic counter-public in the context of the current political crisis in Slovenia, arguing that post-socialist legacies of democratic protest bear a vital role in contesting the conspiracy groups, as well as maintaining the resilience of the liberal democratic ideals of responsible citizenship and common good.